Identification of Germline Mismatch Repair Gene Mutations in Lung Cancer Patients With Paired Tumor-Normal Next Generation Sequencing: A Retrospective Study - Sun, Sibo; Liu, Yiqian; Eisfeld, Ann-Kathrin; Zhen, Fuxi; Jin, Shidai; Gao, Wen; Yu, Tongfu; Chen, Liang; Wang, Wei; Chen, Wei; Yuan, Mingming; Chen, Rongrong; et al. (Frontiers in Oncology, 2019)
Background: Identification of the pathogenic germline mutation in DNA mismatch repair (MMR) genes is one of the diagnostic criteria of Lynch syndrome. In retrospective analysis of germline mutations of lung cancer patients, we accidentally found germline mutations on MMR genes in these patients. As lung cancer is not one of the common manifestation of Lynch syndrome, we aims to investigate whether the development of lung cancer is occasional or related to Lynch syndrome. Methods: We reviewed next-generation sequencing testing results of 1179 lung cancer patients to identify germline mutations on MMR genes including MLH1, MSH2, MSH6 and PMS2. For two patients present with germline mutations, expression of MMR proteins was performed using immunohistochemistry and microsatellite instability (MSI) testing was performed using PCR. Results: Germline mutations on PMS2, MSH2 or MSH6 were detected in 6 patients, and 3 of them had a family history of colon or gastric cancer. The median age at diagnosis was 68.5 years old. Case 1 harbored a frameshift variant in MSH2 (p.E114Rfs*60). Case 2 harbored a nonsense variant in PMS2 (p.R315X). Neither patients’ tumor had loss of MMR protein expression or exhibited MSI and TMB-H. The sister of Case 1 shared the frameshift MSH2 variant, and the son of Case 2 inherited the nonsense PMS2 variant. Conclusion: In this retrospective study, 0.5% (6/1179) of lung cancer patients were found to harbor a germline mutation on MSH2, MSH6 or PMS2. However, two of these patients displayed intact MMR protein expression, MSS and TMB-L. Combined with the baseline characteristics of 6 patients, it seems that lung cancers may not be related to Lynch syndrome. Relationships between the development of lung cancers and Lynch syndrome still requires further large–scale investigations. Nonetheless paired tumor–normal next-generation sequencing can identify germline mutations including that related with Lynch syndrome in cancer patients, which has important implications for cancer screening and risk reduction in these patients and their families.